A Genetic Algorithm for Adaptive Tomography of Elliptical Objects - Venere, Marcelo Javier (2000)
A probabilistic algorithm for on-line tomographic reconstruction of ellipse-like images is presented. The algorithm takes advantage of the characteristic preferential direction of the objects, constructing a guidance function to select the angles for subsequent radiographic projections. The simulation results confirm that the technique reduces the number of projections required to achieve a given quality limit.